Virology analysis in HCV genotype 1-infected patients treated with the combination of simeprevir and TMC647055/ritonavir, with and without ribavirin, and JNJ-56914845 - Leen Vijgen; Kim Thys; An Vandebosch; Pieter Van Remoortere; René Verloes; Sandra De Meyer (Virology Journal, 2017)
Abstract Background In study TMC647055HPC2001, a 3-direct-acting-antiviral (DAA) regimen combining NS3/4A protease inhibitor simeprevir (SMV), non-nucleoside NS5B inhibitor TMC647055/ritonavir (RTV) and NS5A inhibitor JNJ-56914845 resulted in high sustained virologic response 12 weeks after actual end of treatment (SVR12) in chronic hepatitis C virus (HCV) genotype 1-infected patients. SVR12 rates were generally lower in the 2-DAA regimen SMV + TMC647055/RTV with or without ribavirin. The objective of this study was to identify and characterise pre-existing and emerging resistance-associated variants (RAVs) in patients enrolled in study TMC647055HPC2001. Methods HCV population sequencing analyses were performed on baseline isolates from all patients (n = 90) and post-baseline isolates from patients with virologic failure (n = 22). In addition, deep sequencing and phenotypic analyses were performed on selected baseline and post-baseline isolates. Results The majority of patients with virologic failure had emerging RAVs to all study drugs at the time of failure: in all 22 patients SMV RAVs emerged at NS3 positions 80, 155, 156 and/or 168, consistent with the known SMV resistance profile. Emerging TMC647055 RAVs at NS5B position 495 were detected in the majority of patients (16/22), and all 5 patients who failed the 3-DAA regimen had emerging JNJ-56914845 RAVs at NS5A positions 30 and/or 31. While at the end of study emerging SMV and TMC647055 RAVs were no longer observed by population sequencing in 40% (8/20) and 62.5% (10/16) of patients with follow-up data available, respectively, emerging JNJ-56914845 RAVs were still detected in all (5/5) patients. Conclusions Virologic failure in the 2- and 3-DAA combinations was, in the majority of patients, associated with the emergence of RAVs to all study drugs. While emerging SMV and TMC647055 RAVs became undetectable during follow-up, JNJ-56914845 RAVs in NS5A were still observed at end of study. Trial registration number NCT01724086 (date of registration: September 26, 2012)